Clinical features and outcome of Covid-19 in individuals without Comorbidities. Do children have the advantage? - Dr. Abhishek Kumar; Dr. Nilu Kumari; Dr. Ranjeet Kumar Singh; Dr. Alok Kumar; Dr. V K Singh (Pediatric Review: International Journal of Pediatric Research, 2021)
Objective: Information regarding clinical characteristics and the natural course of COVID-19 amongst individuals without comorbidities is scarce. We therefore conducted a retrospective observational study to decipher the disease profile in two different age groups, middle-aged (40-59 years) and children (up to 12 years). Method: Study was conducted by reviewing the medical records of all patients in the desired age groups and excluding all those with preexisting illness (called comorbidities). Result: A total of 154 and 27 patients were enrolled and studied in the middle-aged adults and children group respectively. Males dominated in both groups with a sex ratio of 2.9 in adults and 1.7 in children. Most of the children (92.5%) had a history of exposure from an infected family member, while in the adult group history of contact was present in 71.4% of patients. 62.9% of children had an asymptomatic infection which was significantly higher than 22.8% in adults. Cough and fever were the most common symptoms in both age groups, but adults were more likely to have respiratory complaints when compared with children.11 (7.1%) patients in the adult group had severe disease while in the children group none had severe disease. Similarly in the adult group 11 patients required ICU admission, but none in the children group. The mean duration of RTPCR positivity was similar in both groups. There was 1 (0.6%) expiry in the adult group whereas none in children. Conclusion: Healthy individuals in both middle-aged and children group tend to have milder disease and both harbour the virus for the almost same duration but adults are more symptomatic in comparison to children and hence children are more likely to be potential asymptomatic carrier and transmitter of infection.